2014
DOI: 10.9721/kjfst.2014.46.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antimicrobial Activity and Stability of Orixa japonica Thunb. Leaf Extract

Abstract: The antimicrobial activity of Orixa japonica Thunb. leaf extract towards 13 microorganism strains was evaluated. Both methanol (MEex) and 70% ethanol extracts showed antimicrobial activity towards Streptococcus mutans, Bacillus cereus, Staphylococcus aureus, and Pseudomonas aeruginosa. MEex showed a higher antimicrobial activity than the 70% ethanol extract. In addition, the dichloromethane fraction (DCMfr) of the MEex also had an antimicrobial effect against the microorganisms examined. The minimum inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The compound exhibited larvicidal activity against the fourth-instar larvae of Aedes aegypti , Anopheles sinensis , and Culex pipiens pallens , and it also possessed nematocidal activity against Bursaphelenchus xylophilus and Meloidogynein congnita . Choe et al [ 9 ] reported that the leaf extract of O. japonica showed significant antimicrobial activity against Bacillus cereus , Pseudomonas aeruginosa , Staphylococcus aureus , and Streptococcus mutans . Huang et al [ 10 ] isolated eighteen quinoline alkaloids from the roots of O. japonica , and some of the compounds showed significant anti-pathogenic fungal activity, with one compound demonstrating superior efficacy to that of the positive control hymexazol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound exhibited larvicidal activity against the fourth-instar larvae of Aedes aegypti , Anopheles sinensis , and Culex pipiens pallens , and it also possessed nematocidal activity against Bursaphelenchus xylophilus and Meloidogynein congnita . Choe et al [ 9 ] reported that the leaf extract of O. japonica showed significant antimicrobial activity against Bacillus cereus , Pseudomonas aeruginosa , Staphylococcus aureus , and Streptococcus mutans . Huang et al [ 10 ] isolated eighteen quinoline alkaloids from the roots of O. japonica , and some of the compounds showed significant anti-pathogenic fungal activity, with one compound demonstrating superior efficacy to that of the positive control hymexazol.…”
Section: Introductionmentioning
confidence: 99%
“…A. orixae is the first endophytic fungus of Amphisphaeria that forms a hyphomycetous asexual morph and is unique in undergoing thallic or blastic conidiogenesis and having polymorphic conidia. Thirteen secondary metabolites were identified from the rice fermentation product of A. orixae, including a new isocoumarin, (R)-4,6,8-trihydroxy-5-methylisochroman-1-one (1), and 12 known compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Their chemical structures are depicted in Figure 4 and were established using 1D-and 2D-NMR, mass spectrometry, and chemical computations.…”
Section: Introductionmentioning
confidence: 99%